Uranium adsorbing material and preparation method and use thereof

By introducing amidoxime functional groups on quaternary phosphine modified polyacrylonitrile fibers, the problems of uranium ion adsorption and microbial adhesion in seawater were solved, and materials with high-efficiency adsorption and antibacterial properties were prepared, realizing the Effective extraction of seawater uranium resources.

CN115888674BActive Publication Date: 2024-12-20BEIJING RESEARCH INSTITUTE OF CHEMICAL ENGINEERING AND METALLURGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211466417.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-22
Publication Date
2024-12-20
Estimated Expiration
2042-11-22

AI Technical Summary

Technical Problem

The low concentration of uranium ions in seawater and the presence of a variety of metal ions and microorganisms makes it difficult for existing adsorbent materials to effectively adsorb uranium ions, and the antimicrobial adhesion performance is insufficient, affecting the extraction efficiency and cost of uranium resources.

Method used

Through chemical modification method, amidoxime functional group was introduced on quaternary phosphonium modified polyacrylonitrile fibers, combined with the reaction of potassium chloride, hydroxylamine hydrochloride and potassium carbonate, a kind of uranium ion adsorption effect and antimicrobial adsorption were prepared. Material.

Benefits of technology

The prepared materials show efficient uranium ion adsorption capacity and significant antibacterial properties in simulated seawater, and can be used stably in complex environments for a long time, reducing the cost and difficulty of uranium resource extraction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003956425930000081
    Figure BDA0003956425930000081
  • Figure BDA0003956425930000091
    Figure BDA0003956425930000091
Patent Text Reader

Abstract

The present invention discloses a material for uranium adsorption, a preparation method and a use thereof. The preparation method comprises the following steps: (1) adding 3 to 9 parts by weight of potassium chloride, 10 to 25 parts by weight of hydroxylamine hydrochloride and 10 to 25 parts by weight of potassium carbonate into water and mixing to obtain a mixed solution; (2) adding 0.5 to 2 parts by weight of quaternary phosphonium salt-modified polyacrylonitrile fiber into the mixed solution, reacting at 60 to 80°C for 5 to 20 hours to obtain an intermediate product; (3) adding the intermediate product into an aqueous solution of sodium hydroxide, reacting at 25 to 55°C for 2 to 8 hours to obtain the material for uranium adsorption. The uranium adsorption material prepared by the present invention has a good adsorption effect on uranium ions in seawater and a good anti-microbial adhesion effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a uranium adsorbing material and a preparation method and application thereof. Background Art

[0002] my country's uranium resources have low uranium grade, small deposits, scattered ore bodies, complex rock mineral composition, and high technical difficulty and cost for uranium leaching and recovery. Therefore, it is necessary to explore and develop new uranium resources.

[0003] Seawater is an unconventional uranium resource with great application prospects. The reserves of marine uranium resources are huge. If the technology of extracting uranium from seawater is economical and feasible, the uranium resources in seawater can be used as an effective supplement or substitute for terrestrial uranium resources. At present, due to the low concentration of uranium ions in seawater, the large number of metal ions coexisting with uranium, and the complex environment in seawater, there are problems such as microbial attachment, which seriously affect the adsorption process of uranium ions by the adsorption material. Therefore, it is urgent to develop a material that has a good adsorption effect on uranium ions and resists microbial attachment. Summary of the invention

[0004] In view of this, an object of the present invention is to provide a method for preparing a material for adsorbing uranium, which can be used to prepare a material for extracting uranium from seawater, and has a simple process, low production cost, and can be applied on a large scale.

[0005] Another object of the present invention is to provide a uranium adsorbing material which has a good adsorption effect on uranium ions and is resistant to microbial attachment.

[0006] Another object of the present invention is to provide a use of a material for adsorbing uranium.

[0007] In one aspect, the present invention provides a method for preparing a material for adsorbing uranium, comprising the following steps:

[0008] (1) adding 3 to 9 parts by weight of potassium chloride, 10 to 25 parts by weight of hydroxylamine hydrochloride and 10 to 25 parts by weight of potassium carbonate into water and mixing to obtain a mixed solution;

[0009] (2) adding 0.5 to 2 parts by weight of quaternary phosphonium salt-modified polyacrylonitrile fiber to the mixed solution, reacting at 60 to 80° C. for 5 to 20 hours to obtain an intermediate product;

[0010] (3) adding the intermediate product to an aqueous solution of sodium hydroxide and reacting at 25 to 55° C. for 2 to 8 hours to obtain the uranium adsorbing material;

[0011] Wherein, the mass volume ratio of the quaternary phosphonium salt modified polyacrylonitrile fiber and the water in step (1) is 1g: (190-220)mL.

[0012] The present invention introduces amidoxime functional groups into quaternary phosphonium salt modified polyacrylonitrile fibers by a chemical modification method, and reduces the influence on the antibacterial properties of the materials while ensuring the introduction of amidoxime functional groups by precisely controlling the ratio of each reactant, thereby preparing a material that has a good adsorption effect on uranium ions in seawater and is resistant to microbial adhesion.

[0013] In the present invention, the amount of potassium chloride can be 3 to 9 parts by weight, preferably 4 to 6 parts by weight, and more preferably 5.5 to 6 parts by weight. The amount of hydroxylamine hydrochloride can be 10 to 25 parts by weight, preferably 10 to 20 parts by weight, and more preferably 17 to 20 parts by weight. The amount of potassium carbonate can be 10 to 25 parts by weight, preferably 10 to 20 parts by weight, and more preferably 17 to 20 parts by weight. The amount of quaternary phosphonium salt modified polyacrylonitrile fiber can be 0.5 to 2 parts by weight, preferably 0.8 to 1.5 parts by weight, and more preferably 0.9 to 1 part by weight. The mass volume ratio of quaternary phosphonium salt modified polyacrylonitrile fiber and the water described in step (1) can be 1g: (190 to 220) mL; preferably 1g: (200 to 210) mL. The material obtained in this way has good antibacterial properties and good adsorption of uranium ions.

[0014] According to some embodiments of the present invention, the method for preparing the uranium adsorbing material comprises the following steps:

[0015] (1) adding 4 to 6 parts by weight of potassium chloride, 10 to 20 parts by weight of hydroxylamine hydrochloride and 10 to 20 parts by weight of potassium carbonate into water and mixing them uniformly to obtain a mixed solution;

[0016] (2) adding 0.8 to 1.5 parts by weight of quaternary phosphonium salt-modified polyacrylonitrile fiber to the mixed solution, reacting at 60 to 80° C. for 8 to 12 hours, and washing to obtain an intermediate product;

[0017] (3) adding the intermediate product to an aqueous solution of sodium hydroxide, reacting at 30 to 50° C. for 2 to 6 hours, and washing to obtain the uranium adsorbing material;

[0018] Wherein, the mass volume ratio of the quaternary phosphonium salt modified polyacrylonitrile fiber and the water in step (1) is 1g: (200-210)mL.

[0019] In the present invention, water is preferably one of deionized water, ultrapure water, double distilled water, pure water and distilled water.

[0020] In the present invention, the product needs to be washed after the reaction is completed. The present invention has no special requirements for the washing process, as long as the impurities can be cleaned. The washing method can be one or both of alcohol washing and water washing. In some embodiments, methanol is first used for washing, and then deionized water is used for washing.

[0021] In the present invention, the reaction temperature in step (2) can be 60-80° C., preferably 60-75° C., more preferably 70-75° C. This helps to improve the adsorption performance of the material for uranium ions in seawater.

[0022] In the present invention, in step (3), the mass fraction of sodium hydroxide in the aqueous solution of sodium hydroxide can be 0.3-1.5wt%, preferably 0.4-1.2wt%. The mass volume ratio of the quaternary phosphonium salt-modified polyacrylonitrile fiber and the aqueous solution of sodium hydroxide can be 1g:(100-200)mL, preferably 1g:(150-200)mL.

[0023] According to the preparation method of the present invention, the mass fraction of sodium hydroxide in the aqueous solution of sodium hydroxide is 0.3-1.5wt%;

[0024] The mass volume ratio of the quaternary phosphonium salt modified polyacrylonitrile fiber and the aqueous solution of sodium hydroxide is 1g:(100-200)mL.

[0025] According to some embodiments of the present invention, the mass volume ratio of the quaternary phosphonium salt-modified polyacrylonitrile fiber to the aqueous solution of sodium hydroxide is 1 g: (170-200) mL, which helps to improve the antibacterial property of the material.

[0026] In the present invention, the quaternary phosphonium salt modified polyacrylonitrile fiber can be prepared by conventional methods, preferably by the preparation method of the present invention. The uranium adsorbing material prepared in this way not only has good selectivity and adsorption for uranium in seawater, but also has good antibacterial properties, and can be repeatedly used for long-term extraction of uranium in seawater.

[0027] According to the preparation method of the present invention, the quaternary phosphonium salt modified polyacrylonitrile fiber is prepared by the following steps:

[0028] 1) adding polyacrylonitrile fiber to an alkaline solution, reacting at 50-70° C. for 1-4 hours, and post-treating to obtain pretreated polyacrylonitrile fiber;

[0029] 2) adding the pretreated polyacrylonitrile fiber into a solvent to swell it, then adding a quaternary phosphonium salt and water, reacting at 40-70° C. for 4-10 hours, and post-treating to obtain the quaternary phosphonium salt-modified polyacrylonitrile fiber.

[0030] The post-treatment of the present invention includes washing and drying. The washing method can be one or both of alcohol washing and water washing.

[0031] According to the preparation method of the present invention, the alkali in the alkaline solution is selected from sodium hydroxide and / or potassium hydroxide; the mass volume ratio of the polyacrylonitrile fiber and the alkaline solution is 1g:(100-200)mL.

[0032] In the present invention, the alkali in the alkali solution can be selected from sodium hydroxide and / or potassium hydroxide, preferably sodium hydroxide. The mass concentration of the alkali solution can be 0.4-8wt%, preferably 0.4-1wt%. This helps to uniformly introduce the quaternary phosphonium salt functional group into the polyacrylonitrile fiber.

[0033] In the present invention, the pretreated polyacrylonitrile fiber is added to a solvent for swelling. The solvent may be one or more of methanol, ethanol and water.

[0034] According to the preparation method of the present invention, the solvent is selected from methanol and / or ethanol.

[0035] According to the preparation method of the present invention, the quaternary phosphonium salt is selected from one or more of triphenylbutylphosphonium bromide, triphenyloctylphosphonium bromide and triphenyldodecylphosphonium bromide.

[0036] According to some embodiments of the present invention, the quaternary phosphonium salt is selected from triphenyldodecylphosphonium bromide. According to other embodiments of the present invention, the quaternary phosphonium salt is selected from triphenylbutylphosphonium bromide.

[0037] According to the preparation method of the present invention, the mass ratio of the polyacrylonitrile fiber to the quaternary phosphonium salt is 1:(2-8).

[0038] In certain embodiments, the mass ratio of polyacrylonitrile fiber to the quaternary phosphonium salt is 1:(5-6.5). This can ensure the antibacterial property of the material and reduce the loss of raw materials.

[0039] In another aspect, the present invention provides a material for adsorbing uranium, which is prepared by the above method.

[0040] According to the uranium adsorbing material of the present invention, preferably, the antibacterial rate of the uranium adsorbing material against Escherichia coli is greater than or equal to 85%, and the antibacterial rate against Staphylococcus aureus is greater than or equal to 85%;

[0041] An adsorption test was conducted in simulated seawater with a pH of 8.1 and a uranium mass concentration of 0.3 mg / L. The uranium adsorbing material had an adsorption capacity for uranium ions greater than or equal to 35.6 mg / g.

[0042] According to some preferred embodiments of the present invention, the uranium adsorbing material has an antibacterial rate against Escherichia coli greater than or equal to 96%, and an antibacterial rate against Staphylococcus aureus greater than or equal to 94%; an adsorption test is carried out in simulated seawater with a solution pH of 8.1 and a uranium mass concentration of 0.3 mg / L, and the adsorption capacity of the uranium adsorbing material for uranium ions is greater than or equal to 41.7 mg / g.

[0043] In the present invention, the determination of the antibacterial rate of the material that adsorbs uranium is carried out with reference to GB / T 20944.3-2008.

[0044] In the present invention, simulated seawater refers to natural seawater in which uranyl tricarbonate is added until the concentration of uranium ions in the solution is 0.3 mg / L, and the pH of the simulated seawater solution is 8.1. The concentration of uranium ions in the simulated seawater is measured with reference to HJ700-2014.

[0045] In another aspect, the present invention provides a use of the above-mentioned uranium adsorbing material in extracting uranium from seawater.

[0046] According to some embodiments of the present invention, 0.1 g of the uranium adsorbing material is added to 20 L of simulated seawater, and then placed in a shaker at a speed of 150 r / min for 24 hours. The uranium adsorbing material has an adsorption capacity for uranium ions greater than or equal to 35.6 mg / g.

[0047] The present invention prepares quaternary phosphonium salt modified polyacrylonitrile fiber by a precise functionalization method, and then introduces amidoxime functional groups on the quaternary phosphonium salt modified polyacrylonitrile fiber by a chemical modification method to prepare a material for adsorbing uranium. By adjusting the amount of each reactant, the reaction temperature and other parameters, a material for adsorbing uranium with good adsorption performance for uranium and high antibacterial rate is prepared. The raw material source of the material for adsorbing uranium of the present invention is wide, the preparation process is simple, the production cost is low, and it can be produced on a large scale. DETAILED DESCRIPTION

[0048] The present invention is further described below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited thereto.

[0049] Here is the test method:

[0050] (1) Test of adsorption capacity: 0.1 g of uranium adsorbing material was added to 20 L of simulated seawater (the concentration of uranium ions was 0.3 mg / L and the pH of the solution was 8.1), and then placed in a shaker at a speed of 150 r / min for 24 h. The concentration of uranium ions in the simulated seawater after adsorption, c (in mg / L), was measured, and the adsorption capacity of the material for uranium ions was calculated:

[0051] Adsorption capacity (mg / g) = (0.3-c) × 20 / 0.1;

[0052] Among them, the concentration of uranium ions is tested in accordance with HJ700-2014.

[0053] (2) Test of antibacterial rate: refer to GB / T 20944.3~2008 for testing antibacterial rate.

[0054] Embodiments 1 to 4

[0055] (1) According to the formula in Table 1, 1 g of polyacrylonitrile fiber was added to the alkaline solution for the first reaction. After the reaction was completed, the product was first washed with deionized water and dried naturally to obtain the pretreated polyacrylonitrile fiber.

[0056] (2) 1 g of the pretreated polyacrylonitrile fiber is added to 100 mL of solvent for swelling, and then quaternary phosphonium salt and 100 mL of deionized water are added to obtain a mixture.

[0057] The mixture is placed in a hydrothermal reactor for a second reaction. After the reaction is completed, the product is subjected to a second washing. The second washing process is performed by washing with methanol and deionized water in sequence, and the methanol washing and the deionized water washing constitute a complete washing process, which is repeated multiple times and dried naturally to obtain quaternary phosphonium salt modified polyacrylonitrile fiber.

[0058] (3) Potassium chloride, hydroxylamine hydrochloride, potassium carbonate and 200 mL of deionized water were mixed evenly, and 1 g of the quaternary phosphonium salt-modified polyacrylonitrile fiber was added, and the mixture was placed in an ultrasonic cell crusher for a third reaction. After the reaction was completed, the product was washed with deionized water for a third time to obtain an intermediate product.

[0059] The intermediate product is added to an aqueous solution of sodium hydroxide to carry out a fourth reaction. After the reaction is completed, the product is washed with deionized water to obtain a material for adsorbing uranium.

[0060] The adsorption capacity and antibacterial rate of the uranium adsorbed materials were tested, and the results are shown in Table 2.

[0061] Comparative Example 1

[0062] Except that step (3) is not performed, the rest is the same as Example 1.

[0063] The quaternary phosphonium salt modified polyacrylonitrile fiber prepared in Comparative Example 1 was tested for adsorption capacity and antibacterial rate. The results are shown in Table 2.

[0064] Comparative Example 2

[0065] In Comparative Example 2, step (2) was not performed, and the pretreated polyacrylonitrile fiber was directly used in step (3), and the rest was the same as in Example 1.

[0066] The material prepared in Comparative Example 2 was tested for adsorption capacity and antibacterial rate, and the results are shown in Table 2.

[0067] Comparative Example 3

[0068] Except for the different amounts of raw materials in step (3), the rest is the same as Example 3.

[0069] Specifically, in this comparative example, 4 g of potassium chloride, 8 g of hydroxylamine hydrochloride, 8 g of potassium carbonate and 180 mL of deionized water were uniformly mixed.

[0070] The uranium adsorption material prepared in the above steps was tested for adsorption capacity and antibacterial rate. The results are shown in Table 2.

[0071] Comparative Example 4

[0072] Except for the different mass concentration and amount of the alkaline solution in step (1), the rest is the same as Example 4.

[0073] In this comparative example, the alkaline solution is an aqueous solution of sodium hydroxide, the mass fraction of sodium hydroxide in the aqueous solution of sodium hydroxide is 0.3wt%; the amount of the alkaline solution used is 500mL.

[0074] The uranium adsorption material prepared in the above steps was tested for adsorption capacity and antibacterial rate. The results are shown in Table 2.

[0075] Table 1

[0076]

[0077] Table 2

[0078]

[0079] It can be seen from Table 2 that the adsorption capacity of the uranium adsorbing material of the present invention for uranium ions is greater than or equal to 35.6 mg / g, and the adsorption performance is much greater than that of Comparative Example 1. The antibacterial rate of the uranium adsorbing material of the present invention against Escherichia coli is greater than or equal to 85%, and the antibacterial rate against Staphylococcus aureus is greater than or equal to 85%, and the antibacterial performance is much greater than that of Comparative Example 2.

[0080] Compared with Comparative Examples 3 to 4, the present invention reduces the influence of the preparation process on the antibacterial properties of the material by precisely controlling the ratio of each reactant while fully introducing the amidoxime functional group, thereby preparing a uranium-adsorbing material with good uranium adsorption performance and high antibacterial rate.

[0081] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.

Claims

1. A method for preparing a material for adsorbing uranium, It is characterized in that The steps include: (1) adding 1 g of polyacrylonitrile fiber to 200 mL of a 0.4 wt% sodium hydroxide solution, and performing a first reaction at 50° C. for 4 h; after the reaction, washing the product with deionized water for a total of 6 times, and drying the product naturally to obtain pretreated polyacrylonitrile fiber; (2) adding 1 g of the pretreated polyacrylonitrile fiber into 100 mL of ethanol and swelling at 20° C. for 3 h, and then adding 6.1 g of triphenyl dodecyl phosphonium bromide and 100 mL of deionized water to obtain a mixture; The mixture was placed in a hydrothermal reactor for a second reaction at 60° C. for 8 hours; after the reaction, the product was subjected to a second washing, which was performed 5 times in total; The second washing process uses methanol and deionized water to wash in sequence, and the methanol washing and deionized water washing constitute a complete washing process. After washing, it is naturally dried to obtain quaternary phosphonium salt modified polyacrylonitrile fiber; (3) 6 g of potassium chloride, 20 g of hydroxylamine hydrochloride, 20 g of potassium carbonate and 200 mL of deionized water were mixed evenly, and 1 g of quaternary phosphonium salt-modified polyacrylonitrile fiber was added, and the mixture was placed in an ultrasonic cell crusher at 75° C. for a third reaction for 12 h; after the reaction, the product was washed with deionized water for a third time, and the third washing was performed 8 times in total to obtain an intermediate product; The intermediate product is added to 170 mL of an aqueous solution of sodium hydroxide having a concentration of 0.6 wt %, and a fourth reaction is carried out at 50° C. for 4 hours; after the reaction is completed, the product is washed with deionized water for a fourth time, and the fourth washing is carried out 10 times in total to obtain a material for adsorbing uranium; The uranium adsorbing material has an antibacterial rate of 96% on Escherichia coli, an antibacterial rate of 94% on Staphylococcus aureus, and an adsorption capacity of uranium ions of 41.7 mg / g.

Citation Information

Patent Citations

  • Phosphonium salt modified acrylic fibre antibacterial material and preparation method thereof

    CN103266473A

  • Amidoximated polyacrylonitrile spinning solution and nanoscale ion exchange fiber prepared from solution

    CN105568423A

  • Antibacterial amidoxime-group seawater-extracted uranium absorbent and preparation method thereof

    CN107138137A

  • Antibacterial uranium extraction fiber and preparation method thereof

    CN109371500A

  • Anti-biofouling hydrogel film material for extracting uranium from seawater and preparation method thereof

    CN112516975A